2008
DOI: 10.1158/1535-7163.mct-08-0327
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic catastrophe cell death induced by heat shock protein 90 inhibitor in BRCA1-deficient breast cancer cell lines

Abstract: Heat shock protein 90 (Hsp90) is a molecular chaperone involved in folding, assembly, maturation, and stabilization of the client proteins that regulate survival of malignant cells. As previous reports correlate high Hsp90 expression with decreased survival in breast cancer, Hsp90 may be a favorable target for investigational therapy in breast cancer. In our study, we have examined the response of a panel of both BRCA1-null (UACC 3199, HCC 1937, and MBA-MD-436) and BRCA1-wt breast cancer cell lines (MCF-7, MBA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The two BLBC cell lines used in our experiments both express wild-type BRCA1 protein and are proficient in radiation-induced DNA DSB repair [44, 45]. KU70/80 and DNA-PKcs are of vital importance in NHEJ, the predominant pathway for the repair of radiation-induced DSBs in human cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…The two BLBC cell lines used in our experiments both express wild-type BRCA1 protein and are proficient in radiation-induced DNA DSB repair [44, 45]. KU70/80 and DNA-PKcs are of vital importance in NHEJ, the predominant pathway for the repair of radiation-induced DSBs in human cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of the Hsp90 inhibition are very complex and depend on the biochemical features and molecular background of treated cells [42]. The reported cell cycle effects are mostly G1 and G2/M arrest [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data are in agreement with previous reports demonstrating that the induction of cell cycle arrest of breast cancer cells is associated with increased expression of cyclin G1, CHEK1, CDKN1C (p57, Kip2), GADD45A, and E2F2. [34][35][36][37][38] In addition, cycle arrest of MDA-MB-231 cells can be mediated by the inhibition of cyclin A1 and CDK6. 39,40 In this study, we found that BD suppresses invasive behavior of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%